Comparison of standard polymer formula versus short peptide formula in sepsis patients with acute gastrointestinal injury - Wang, Youquan; Li, Yanhua; Zhang, Yuhan; Zhang, Dong (Frontiers in Nutrition, 2025)
BackgroundTo investigate the selection of enteral nutrition (EN) formulas for critically ill sepsis patients with acute gastrointestinal injury (AGI) grade I-II.MethodsWe conducted a retrospective cohort study on critically ill sepsis patients with AGI grades I-II. The primary outcomes were EN caloric adequacy on day 7, calories and protein gain from EN within 3–7 days, and the incidence of gastric retention and diarrhea after EN administration. We performed a subgroup analysis based on whether patients initiated EN within 48 h.ResultsIn the early EN subgroup, caloric adequacy, calories and protein gain of EN on day 7 of the short-peptide group was higher than that of the standard-polymeric group (59.1% vs. 27.3%, p = 0.001; 624[0, 936] vs. 0[−360, 480], p = 0.001; 24[0, 38] vs. 0[−14.4, 19.2], p = 0.003, respectively), and the incidence of gastric retention (18.2% vs. 36.4%, p = 0.03) and diarrhea (9.1% vs. 25.5%, p = 0.02) were lower in the short-peptide group than in the standard-polymeric group. However, in the delayed EN subgroup, the caloric adequacy of EN on day 7 of the short-peptide group was lower than that of the standard-polymeric group (28.6% vs. 43.5%, p = 0.02), calories and protein gain from EN were lower in the short-peptide group than in the standard-polymeric group (960[480, 1,200] vs. 1,080[720, 1,440], p = 0.04; 38.4[19.2, 50.4] vs. 43.2[28.8, 57.6], p = 0.04, respectively).ConclusionIn sepsis patients with AGI grades I–II, short-peptide formulas may be considered for early EN initiation (≤48 h), while standard-polymer formulas may be an option for late EN initiation (>48 h). Exploratory results need to be interpreted with caution and await verification of these findings through high-quality research.